POLITICAL DYSTOPIA IN SUZANNE COLLINS’ THE HUNGER GAMES - Siswantia Sar; Sri Minda Murni (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2012)
The study deals with the aspects of political dystopia in Suzanne Collins’ The Hunger Games. The objective of study is to describe the aspects of political dystopia occur in Suzanne Collins’ The Hunger Games. The data were analyzed by identifying the statements found in Suzanne Collins’ The Hunger Games. The findings show that there are five aspects of political dystopia occur in the novel. The five aspects are: a) Totalitarian Government, b) Political Repression, c) Dehumanization, d) Restrictions of Freedom, e) Oppression which Led to the Rebellion. From those aspects, it is concluded that political dystopia occur in Suzanne Collins’ The Hunger Games. Keyword        : prose, novel, science fiction, political dystopia